2001
DOI: 10.1034/j.1600-0463.2001.d01-178.x
|View full text |Cite
|
Sign up to set email alerts
|

Early dissemination of Borrelia burgdorferi without generalized symptoms in patients with erythema migransNote

Abstract: The diagnosis of erythema migrans (EM) is not always easy, and reports of culture- or PCR-confirmed diagnosis as well as reports of EM with simultaneous disseminated disease are few. Characteristics and incidence of EM in addition to frequency of early dissemination of B. burgdorferi were studied in the archipelago of South-Western Finland prospectively using questionnaires, skin biopsies and blood samples. Clinical EM was recognized in 82 patients (incidence 148/100,000 inhabitants/year). Of skin biopsy sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…As an ELISA antigen, recombinant DbpB from B. garinii predominated. This is in line with European studies, in which either B. garinii or B. afzelii has been observed to be the most prevalent strain causing human LB [26][27][28]. In patients with LA from Germany, the DbpB from B. burgdorferi sensu stricto also performed well as an ELISA antigen.…”
Section: Discussionsupporting
confidence: 73%
“…As an ELISA antigen, recombinant DbpB from B. garinii predominated. This is in line with European studies, in which either B. garinii or B. afzelii has been observed to be the most prevalent strain causing human LB [26][27][28]. In patients with LA from Germany, the DbpB from B. burgdorferi sensu stricto also performed well as an ELISA antigen.…”
Section: Discussionsupporting
confidence: 73%
“…Recent reports from the USA and Europe (Oksi et al, 2001;Smith et al, 2002) have shown that the diagnosis of EM solely on clinical grounds may be difficult. During the first few days of infection, the pathognomonic expanding peripheral erythema with a central clearing appears to be far less common than lesions with homogeneous redness (Oksi et al, 2001;Smith et al, 2002).…”
Section: Antibodies In the Convalescent Phasementioning
confidence: 99%
“…During the first few days of infection, the pathognomonic expanding peripheral erythema with a central clearing appears to be far less common than lesions with homogeneous redness (Oksi et al, 2001;Smith et al, 2002). This implies that EM may be confused with other similar rashes, e.g.…”
Section: Antibodies In the Convalescent Phasementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relative distribution of different Borrelia genospecies in different geographical locations may explain the somewhat discrepant serological responses. Such differences have previously been documented: In a Finnish study, the majority of culture or PCR verified EM patients were positive for B. garinii (Oksi et al, 2001) while a recent Swedish study from Blekinge County showed a predominance of B. afzelii in a comparable patient material (Bennet et al, 2006).…”
Section: Discussionmentioning
confidence: 95%